Double-strategy modified high-nickel positive electrode material and preparation method and application thereof
By adopting a dual modification strategy on high-nickel positive electrode materials, the fast ion conductor cladding and bulk phase doping are solved, and the irreversible phase change and structural degradation of high-nickel positive electrode materials in the deep deliques state are significantly improved, which significantly improves the rate performance and cycle stability of the battery.
Patent Information
- Application Number
- CN202510049850.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-13
- Publication Date
- 2025-05-02
AI Technical Summary
The existing high-nickel positive electrode materials are prone to irreversible phase transformation and structural degradation in the deep deliquency state, affecting the cycle stability and safety of the battery.
Using a dual modification strategy, a substrate of LiNi1-x-yCoxMnyO2 is formed by forming a fast ion conductor LiLaO2 clad layer on the surface of the high-nickel positive electrode material and doping Y elements in the body phase.
It effectively reduces the corrosion of the electrolyte on active substances, provides fast ion conduction paths, reduces internal resistance, and improves the rate performance and cycle stability of the battery.
Smart Images

Figure CN119920878A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of cathode materials for lithium-ion batteries, and particularly relates to a dual-modification strategy modified high-nickel cathode material, a preparation method thereof, and an application thereof. Background Art
[0002] Lithium-ion batteries have gradually become the main power source for modern electronic devices such as portable electronic products, electric vehicles, and large-scale energy storage devices due to their advantages such as high energy density and long cycle life. With the wide application of lithium-ion batteries, the growing social demand has put forward higher requirements for lithium-ion batteries. The cathode material of a lithium-ion battery is one of the important factors determining the battery performance. In order to conform to the progress of the times, it is urgent to optimize and develop cathode materials with high energy density, long cycle stability, high safety, and low cost. Through strategies such as structural regulation and surface coating of the cathode material, the cycle stability of the structure can be effectively regulated, and the long cycle stability and high rate performance of the battery can be achieved.
[0003] Currently, the commercially available cathode materials for lithium-ion batteries mainly include LiCoO2, LiMnO4, LiFePO4, etc. The actual specific capacities of these materials are all lower than 200 mAh g -1 , which cannot meet the high requirements for the performance of current lithium-ion batteries. The high-nickel cathode material LiNi 1-x-y Co x Mn y O2, where 0.8 ≤ (1 - x - y) < 1, 0 < x < 0.2, 0 < y < 0.2, has a higher theoretical specific capacity (>250 mAh g -1 ) and a wide voltage range (2.7 - 4.3 V vs. Li + / Li), and is expected to become the cathode material for the next generation of high-energy density lithium-ion batteries. A large number of studies have shown that the direct contact between the cathode and the organic electrolyte accelerates the catalytic decomposition of the electrolyte. This leads to irreversible reactions, hinders the electrochemical kinetics, and reduces the cycle stability. Generally, when the high-nickel cathode reaches a deep de-lithiation state (voltage > 4.3 V), nickel ions mainly exist in the form of highly oxidized Ni 4+ , resulting in the release of lattice oxygen, and ultimately leading to the deterioration of thermal stability. During the process of lithium ion extraction, Li + (with a radius of ) is similar in size to Ni 2+ , resulting in the migration of Ni 2+ ions through the tetrahedral interstitial sites, occupying the Li + in the lithium layer.Vacancies. These adverse reactions destroy the ordered layered structure of the material, leading to the formation of irreversible phase transitions, such as the formation of spinel and rock salt phases. In addition, the phase transition from H2 to H3 during charging leads to a sudden contraction of the lattice in the c-axis direction, uneven distribution of mechanical stress inside the grains, and ultimately the rupture of secondary particles. At the same time, a new cathode-electrolyte interface is exposed, further exacerbating the degradation of the structure and the decline of electrochemical performance.
[0004] The dual modification strategy of bulk doping and surface coating has been proven to effectively improve the cycle performance of high-nickel cathode materials. Through bulk doping, the doping elements form stable strong metal-oxygen (MO) bonds with lattice oxygen, which not only inhibits the lattice distortion and cracking of the lattice during long cycles, but also enhances the kinetics of lithium ion migration. The surface coating strategy can form a uniform protective layer on the surface of the high-nickel cathode, which helps to inhibit the structural damage caused by surface side reactions and ultimately achieve the long-cycle stability of the high-nickel cathode material. However, a single modified doping still exposes the high-nickel cathode material directly to the electrolyte, which is prone to cause unnecessary side reactions, thereby affecting the safety and long-term stability of the battery. A single coating method is also difficult to stabilize the crystal structure of the bulk phase during long-term cycles, resulting in a gradual decline in the performance of the material. Summary of the invention
[0005] The purpose of the present invention is to provide a nickel positive electrode material with high modification by a double modification strategy and a preparation method and application thereof, so as to solve the problem of instability of batteries prepared by a single modification doping or a single coating method.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions:
[0007] The invention discloses a high-nickel cathode material modified by a double modification strategy, wherein the substrate is a high-nickel cathode material, a fast ion conductor coating layer is provided on the surface of the substrate, the fast ion conductor coating layer is LiLaO2, and Y is doped in the bulk phase to replace Ni.
[0008] Among them, the chemical formula of high nickel positive electrode material is: LiNi 1-x-y Co x Mn y O2, where 0.8≤(1-xy)<1,0 <x<0.2,0<y<0.2。
[0009] Furthermore, the thickness of the fast ion conductor coating layer is 5 to 30 nm.
[0010] The present invention also discloses a method for preparing the high-nickel positive electrode material modified by the dual strategy, comprising the following process:
[0011] The high nickel precursor Ni 1-x-y Co x Mny (OH)2 is ultrasonically dispersed in anhydrous ethanol solution to form a precursor suspension;
[0012] Dissolve soluble lanthanum salt and yttrium salt in anhydrous ethanol to form a colorless and transparent solution;
[0013] Add the colorless transparent solution to the precursor suspension, continue to heat with constant temperature stirring for 8 to 12 hours until the solution is completely evaporated, and collect the solid phase product;
[0014] The solid phase product is mixed evenly with the lithium salt, and then heat treated in an oxygen atmosphere, and naturally cooled to obtain a high nickel positive electrode material modified by a dual strategy;
[0015] The total mass of the lanthanum salt and the yttrium salt is 0.3wt% to 0.7wt% of the high nickel precursor;
[0016] The double-strategy modified high-nickel positive electrode material is a high-nickel positive electrode material with a fast ion conductor LiLaO2 coating layer and bulk Y doping.
[0017] Furthermore, the lanthanum salt is lanthanum nitrate or lanthanum acetate.
[0018] Furthermore, the yttrium salt is yttrium nitrate or yttrium acetate.
[0019] Furthermore, the lithium salt is lithium hydroxide or lithium carbonate.
[0020] Furthermore, in the constant temperature stirring heating, the heating temperature is 60-100°C.
[0021] Furthermore, the heat treatment temperature is 700-800°C and the time is 12-15h.
[0022] Further, the molar ratio of the lanthanum salt to the yttrium salt is 1:1;
[0023] The molar ratio of the solid phase product to the lithium ions in the lithium salt is 1:1.03-1.05.
[0024] The present invention also discloses the application of the dual strategy modified high nickel cathode material in the preparation of lithium ion batteries. The working voltage of the prepared lithium ion battery can be increased to 4.4V, and the discharge specific capacity at a current density of 0.1C is greater than 224mAh g -1 .
[0025] Compared with the prior art, the present invention has the following beneficial technical effects:
[0026] The present invention discloses a high-nickel cathode material modified by a dual strategy, which has a fast ion conductor LiLa2O coating layer, which can not only reduce the corrosion of the electrolyte to the active material, but also provide a fast ion conduction path, reduce the internal resistance of the high-nickel cathode material during high-rate discharge, improve the rate performance of the battery, and make the battery more stable during fast charging and discharging. Appropriate amount of bulk phase doping can improve the crystal structure and electrochemical properties of the material, thereby improving the comprehensive performance of the material, such as increasing specific capacity and improving charge and discharge efficiency.
[0027] Furthermore, the thickness of the fast ion conductor coating is 5 to 30 nm. If the coating is too thin, it is difficult to effectively isolate the positive electrode material from the electrolyte, which may lead to side reactions and affect the material's cycle stability. If the coating is too thick, it may hinder the migration path of lithium ions, increase internal resistance, and reduce the battery's conductivity and rate performance. The right amount of doping can improve performance, but too much doping may cause structural instability of the material, and may even lead to too strong interactions between atoms, resulting in adverse electrochemical reactions, which in turn affect the battery's performance and service life.
[0028] The purpose of the present invention is to provide a method for preparing a double-modified high-nickel positive electrode material, which adopts a wet chemical method to coat lanthanum salt and yttrium salt, and then realizes the high-nickel positive electrode material with bulk Y doping and LiLaO2 surface coating coating in the subsequent high-temperature sintering process, which effectively reduces the lattice distortion and collapse caused by the complex irreversible phase change in the cycle process. During the high-temperature sintering process, if the sintering temperature is higher than 800°C, excessive volatilization of lithium salt and loss of transition metal ions will be caused. If the sintering temperature is lower than 700°C, it will cause problems such as poor crystallinity and low capacity of the sample. The coated fast ion conductor can provide an ion conduction path, which helps to promote the rapid migration of lithium ions and improve the ionic conductivity of the battery. In addition, the appropriate coating thickness can effectively inhibit electrolyte corrosion and side reactions at the interface. Combined with the advantages of bulk doping, the lithium ion kinetics are significantly improved, thereby improving chemical stability and rate performance. Therefore, the prepared double-modified high-nickel cathode material has a discharge capacity of more than 224 mAh g at a current density of 0.1 C when the working cut-off voltage is 4.4 V. -1 Therefore, the high nickel cathode material that achieves dual modification of bulk doping and surface coating in one step not only combines the advantages of the two modification strategies, but also reduces production costs and simplifies the process flow while ensuring the performance of the high nickel cathode material. This innovative dual modification technology not only improves the overall performance of the material, but also provides reliable technical support for future large-scale industrial production, promoting the application and development of high energy density batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 X-ray diffraction patterns of the double-modified high-nickel positive electrode material prepared in Example 1 and the sample prepared in Example 2.
[0030] Figure 2 This is a transmission electron microscope image of the high-nickel positive electrode material prepared in Example 1.
[0031] Figure 3 The cycling performance of the high nickel cathode material prepared in Example 2 is compared with that of the unmodified high nickel cathode material (NCM) under 1C test conditions.
[0032] Figure 4 This is a rate performance diagram of the high nickel positive electrode material prepared in Example 1 and Example 2. DETAILED DESCRIPTION
[0033] In order to make the purpose, technical solutions and advantages of the present invention clearer, the following is further described in detail with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention, that is, the embodiments described are only part of the embodiments of the present invention, not all embodiments. Based on the drawings and embodiments of the present invention, all other embodiments obtained by those skilled in the art without making creative work belong to the protection scope of the present invention.
[0034] The features and performances of the present invention are further described in detail below in conjunction with the embodiments.
[0035] Example 1
[0036] (1) 10 g Ni 0.9 Co 0.05 Mn 0.05 The (OH)2 precursor powder is ultrasonically dispersed in 300 mL of anhydrous ethanol solution to form a brown suspension, which serves as a precursor suspension containing a high-nickel positive electrode material.
[0037] (2) Weigh metal La salt and Y salt in a mass ratio of 0.3 wt% of the precursor powder, specifically:
[0038] 0.0159 g of soluble lanthanum nitrate and 0.0141 g of yttrium nitrate were weighed and dissolved in anhydrous ethanol at a molar ratio of 1:1 to form a colorless transparent solution.
[0039] (3) A colorless transparent solution containing metal La salt and Y salt is added dropwise into a precursor suspension containing a high-nickel cathode material, and heated in an oil bath with constant stirring for 8 h at a temperature of 80°C until the solution is completely evaporated, and the solid phase product is collected.
[0040] (4) The solid phase product collected above was mixed evenly with lithium ions in lithium hydroxide at a molar ratio of 1:1.03, and heat treated in an oxygen atmosphere at a temperature of 730°C for 12 hours. After natural cooling, a double-modified high-nickel positive electrode material was obtained, which was marked as 0.3%-La-Y-NCM.
[0041] The double-modified high-nickel cathode material prepared in this embodiment has an X-ray diffraction pattern (XRD) as shown in Figure 1 shown. Figure 1 The XRD diffraction peaks in LiNi 0.9 Co 0.05 Mn 0.05 The O2 crystal phase is well matched, indicating that the dual modification strategy for modifying high-nickel positive electrode materials will not destroy their crystal structure.
[0042] The fast ion conductor LiLaO2 coating layer and bulk Y-doped high nickel positive electrode material prepared in this embodiment have transmission electron microscope (TEM) images as shown in FIG. Figure 2 shown. Figure 2 The lattice fringe spacing of the surface phase is 0.144nm and 0.212nm, corresponding to the (241) and (130) crystal planes of LiLaO2, respectively; the lattice fringe spacing of the internal crystal is 0.245nm, corresponding to the LiNi 0.9 Co 0.05 Mn 0.05 The results show that the fast ion conductor LiLaO2 is successfully coated on LiNi 0.9 Co 0.05 Mn 0.05 O2 surface, the coating thickness is about 7 to 10 nm.
[0043] Battery performance test: The prepared high nickel cathode material modified by the double modification strategy was mixed with conductive carbon black and binder polyvinylidene fluoride in a mass ratio of 8:1:1 to form cathode slurry, in which organic solvent N-methylpyrrolidone (NMP) was used as solvent. After stirring for 8 hours, a uniform slurry was obtained, which was then evenly coated on the current collector aluminum foil and dried in a vacuum oven at 120°C for 12 hours. Subsequently, the dried pole piece was punched into a disc with a diameter of 12 mm, and a CR2025 button cell was assembled in a glove box filled with argon atmosphere, in which a lithium sheet was used as the counter electrode, a Celgard2400 diaphragm was used, and the electrolyte composition was a mixed solution of 1 mol / L LiPF6 dissolved in EC and DMC (EC / DMC volume ratio 1:1).
[0044] The prepared lithium-ion battery was subjected to rate performance test after being left for 12 hours. Figure 4As shown in the figure, the discharge specific capacity of the modified samples at different rates is significantly improved compared with the original samples (NCM).
[0045] Example 2
[0046] (1) Ni 0.9 Co 0.05 Mn 0.05 The (OH)2 precursor powder is ultrasonically dispersed in 300 mL of anhydrous ethanol solution to form a brown suspension, which serves as a precursor suspension containing a high-nickel positive electrode material.
[0047] (2) Weigh metal La salt and Y salt in a mass ratio of 0.5 wt% of the precursor powder, specifically:
[0048] 0.0233 g of soluble lanthanum acetate and 0.0267 g of yttrium nitrate were weighed and dissolved in anhydrous ethanol at a molar ratio of 1:1 to form a colorless transparent solution.
[0049] (3) A colorless transparent solution containing metal La salt and Y salt is added dropwise into a precursor suspension containing a high-nickel cathode material, and heated in an oil bath with constant temperature stirring for 10 h at 100° C. until the solution is completely evaporated, and the solid phase product is collected.
[0050] (4) The collected powder obtained above was mixed evenly with lithium ions in lithium hydroxide at a molar ratio of 1:1.05, and heat treated in an oxygen atmosphere at a temperature of 700°C for 15 hours. After natural cooling, a double-modified high-nickel positive electrode material was obtained, which was marked as 0.5%-La-Y-NCM.
[0051] The double-modified high-nickel cathode material prepared in this embodiment has an X-ray diffraction pattern (XRD) as shown in Figure 1 shown. Figure 1 The XRD diffraction peaks in LiNi 0.8 Co 0.1 Mn 0.1 The O2 crystal phase matches well, indicating that the coating process will not destroy the crystal structure of the high-nickel positive electrode material.
[0052] Battery performance test: The prepared high-nickel positive electrode material was mixed with conductive carbon black and binder polyvinylidene fluoride in a mass ratio of 8:1:1 to form a positive electrode slurry, in which organic solvent N-methylpyrrolidone (NMP) was used as the solvent. After stirring for 8 hours, a uniform slurry was obtained, which was then evenly coated on the current collector aluminum foil and dried in a vacuum oven at 120°C for 12 hours. Subsequently, the dried pole piece was punched into a disc with a diameter of 12 mm, and a CR2025 button cell was assembled in a glove box filled with argon atmosphere, in which a lithium sheet was used as the counter electrode, a Celgard2400 diaphragm was used, and the electrolyte composition was a mixed solution of 1 mol / L LiPF6 dissolved in EC and DMC (EC / DMC volume ratio 1:1).
[0053] The prepared lithium-ion battery was placed for 12 hours for cycle performance and rate performance tests. Figure 3 As shown in Figure 2, the operating cut-off voltage is 4.4 V and the discharge capacity at a current density of 0.1 C is greater than 224 mAh g -1 After 100 cycles at 1C current density, the capacity retention rate is 90.2%.
[0054] Rate performance Figure 4 As shown in the figure, the discharge specific capacity of the modified samples at different rates is significantly improved compared with the original samples (NCM).
[0055] Example 3
[0056] (1) 10 g Ni 0.9 Co 0.05 Mn 0.05 The (OH)2 precursor powder is ultrasonically dispersed in 300 mL of anhydrous ethanol solution to form a brown suspension, which serves as a precursor suspension containing a high-nickel positive electrode material.
[0057] (2) Weigh metal La salt and Y salt in a mass ratio of 0.7 wt% of the precursor powder, specifically:
[0058] 0.038 g of soluble lanthanum acetate and 0.032 g of yttrium acetate were weighed and dissolved in anhydrous ethanol at a molar ratio of 1:1 to form a colorless transparent solution.
[0059] (3) A colorless transparent solution containing metal La salt and Y salt is added dropwise into a precursor suspension containing a high-nickel cathode material, and heated in an oil bath at a constant temperature of 80°C for 10 h until the solution is completely evaporated, and the solid phase product is collected.
[0060] (4) The collected powder obtained above was mixed evenly with lithium ions in lithium hydroxide at a molar ratio of 1:1.05, and heat treated in an oxygen atmosphere at a temperature of 750°C for 12 hours. After natural cooling, a double-modified high-nickel positive electrode material was obtained, which was marked as 0.7%-La-Y-NCM.
[0061] Example 4
[0062] (1)Ni 0.8 Co 0.1 Mn 0.1 The (OH)2 precursor powder is ultrasonically dispersed in 300 mL of anhydrous ethanol solution to form a brown suspension, which serves as a precursor suspension containing a high-nickel positive electrode material.
[0063] (2) Weigh metal La salt and Y salt in a mass ratio of 0.3 wt% of the precursor powder, specifically:
[0064] 0.0163 g of soluble lanthanum acetate and 0.0137 g of yttrium acetate were weighed and dissolved in anhydrous ethanol at a molar ratio of 1:1 to form a colorless transparent solution.
[0065] (3) Add a colorless transparent solution containing metal La salt and Y salt dropwise into the precursor suspension containing high-nickel positive electrode material, and heat in an oil bath for 10 h at a constant temperature of 120°C until the solution is completely evaporated, and collect the solid phase product.
[0066] (4) The powder collected above was mixed evenly with lithium ions in lithium carbonate at a molar ratio of 1:0.525, and heat treated in an oxygen atmosphere at a temperature of 800° C. for 15 h. After natural cooling, a double-modified high-nickel positive electrode material was obtained.
[0067] The preparation method of the double-modified high-nickel positive electrode material designed by the present invention uses a wet chemical method to form a uniform coating of lanthanum salt and yttrium salt on the surface of the precursor of the high-nickel positive electrode material, and uses the competitive principle of the same main group elements to form a fast ion conductor coating layer and bulk element doping on the surface during high-temperature sintering. The fast ion conductor coating layer can not only effectively isolate the direct contact between the positive electrode material and the electrolyte to inhibit interfacial side reactions, reduce the precipitation, corrosion and structural degradation of the surface lattice oxygen, but also provide a fast transport channel for lithium ions, thereby improving the lithium ion migration kinetics and improving the rate performance of the battery. Bulk element doping can optimize the crystal structure, improve the conductivity of the material, and enhance the structural stability of the material.
[0068] The fast ion conductor coating can provide additional ion channels, promote the conduction of ions on the surface of the positive electrode material, reduce the interface impedance, and improve the rate performance of the battery. Doping elements can optimize the crystal structure of the positive electrode material, relieve the stress generated during the charge and discharge process, thereby reducing phase change and structural degradation and improving its structural stability.
[0069] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the specific implementation methods of the present invention can still be modified or replaced by equivalents. Any modification or equivalent replacement that does not depart from the spirit and scope of the present invention should be covered within the scope of protection of the claims of the present invention.
Claims
1. A high nickel cathode material modified by a dual strategy, characterized in that: The substrate is a high-nickel positive electrode material, and the substrate surface has a fast ion conductor coating layer, the fast ion conductor coating layer is LiLaO2, and Y is doped in the bulk phase to replace Ni. Among them, the chemical formula of high nickel positive electrode material is: LiNi 1-x-y Co x Mn y O2, where 0.8≤(1-xy)<1,0 <x<0.2,0<y<0.2。 2. The high nickel cathode material modified by dual strategy according to claim 1, characterized in that: The thickness of the fast ion conductor coating layer is 5 to 30 nm.
3. The method for preparing the high nickel cathode material modified by the dual strategy according to claim 1 or 2, characterized in that: The following steps are involved: The high nickel precursor Ni 1-x-y Co x Mn y (OH)2 is ultrasonically dispersed in anhydrous ethanol solution to form a precursor suspension; Dissolve soluble lanthanum salt and yttrium salt in anhydrous ethanol to form a colorless and transparent solution; Add the colorless transparent solution to the precursor suspension, continue to heat with constant temperature stirring for 8 to 12 hours until the solution is completely evaporated, and collect the solid phase product; The solid phase product is mixed evenly with the lithium salt, and then heat treated in an oxygen atmosphere, and naturally cooled to obtain a high nickel positive electrode material modified by a dual strategy; The total mass of the lanthanum salt and the yttrium salt is 0.3wt% to 0.7wt% of the high nickel precursor; The double-strategy modified high-nickel positive electrode material is a high-nickel positive electrode material with a fast ion conductor LiLaO2 coating layer and bulk Y doping.
4. The method for preparing the high-nickel cathode material modified by dual strategy according to claim 3, characterized in that: The lanthanum salt is lanthanum nitrate or lanthanum acetate.
5. The method for preparing the high-nickel cathode material modified by the dual strategy according to claim 3, characterized in that: The yttrium salt is yttrium nitrate or yttrium acetate.
6. The method for preparing the high nickel cathode material modified by the dual strategy according to claim 3, characterized in that: The lithium salt is lithium hydroxide or lithium carbonate.
7. The method for preparing the dual strategy modified high nickel cathode material according to claim 3, characterized in that: In the constant temperature stirring heating, the heating temperature is 60-100°C.
8. The method for preparing the dual strategy modified high nickel positive electrode material according to claim 3, characterized in that: The heat treatment temperature is 700-800°C and the time is 12-15h.
9. The method for preparing the dual strategy modified high nickel positive electrode material according to claim 3, characterized in that: The molar ratio of lanthanum salt to yttrium salt is 1:1; The molar ratio of the solid phase product to the lithium ions in the lithium salt is 1:1.03-1.
05.
10. The use of the dual strategy modified high nickel cathode material according to claim 1 or 2 in the preparation of lithium ion batteries, characterized in that: The working voltage of the prepared lithium-ion battery can be increased to 4.4V, and the discharge capacity at a current density of 0.1C is greater than 224mAh g -1 .
Citation Information
Cited By
Positive electrode material, preparation method thereof and lithium ion battery
CN121839671A
Modified high-nickel positive electrode material adaptive to high-voltage system as well as preparation method and application of modified high-nickel positive electrode material
CN122202257A
Fast ion conductor-electron conductor positive electrode material precursor and preparation method thereof
CN122426794A